Tourism, economic growth, and environmental pollution in APEC economies, 1995-2020: An econometric analysis of the Kuznets hypothesis - César Lenin Navarro-Chávez; Francisco Javier Ayvar-Campos; Celeste Camacho-Cortez (Economies, 2023)
Tourism plays an important role in fostering economic growth within the Asia-Pacific Economic Cooperation (APEC) forum member countries. Nevertheless, the development of this sector has resulted in significant depletion of natural resources and pollution. This research aims to determine the relationship between tourism, economic growth, and environmental pollution in both developing and developed APEC economies from 1995 to 2020. By adopting the Environmental Kuznets Curve (EKC) framework, two dynamic panel data models are estimated employing Dynamic Ordinary Least Squares (DOLS), and causal relationships are established using the Dumitrescu- Hurlin test. The results indicate that tourism and economic growth have had a positive influence on the rise of environmental pollution in both groups of economies during the specified period. This research offers new insights by analyzing twelve developing and nine developed APEC economies over a span of 25 years, estimating two DOLS models, conducting Dumitrescu-Hurlin causality tests, and presenting evidence of EKC for both types of economies. Consequently, the implementation of policies that foster the preservation of natural areas, the utilization of renewable energies, and the promotion of sustainable tourism practices is recommended.
Keywords: 330; tourism; economic growth; environmental pollution; APEC